Finalités, conditions, intérêts et limites d'une collaboration enseignants, formateurs et chercheur. Un exemple en mathématiques à propos d'une injonction institutionnelle adressée aux enseignants du primaire - Magali Hersant (Nantes Université, 2010)
In 2002, a new mathematics curriculum for the primary school asks teachers to use a new kind of problems in their classes: « les problèmes pour chercher ». Since primary school teachers are polyvalent teachers, we created a working group to help them achieve this new objective, which was comprised of primary school teachers, mathematics teachers, and researchers in didactics of mathematics. The goal was to develop didactical situations that fit the characteristics of "problèmes pour chercher". This paper is a retrospective study of this collaboration. We first spell out the different status of the participants in this collaboration, together with their individual aims and common goals. We also present the theoretical framework and the methodology that was used in the group. We then analyze from the objective evolution of a didactical situation how the knowledge originating from the teacher practice and from research both contribute to this evolution. Next, some limits of the work are pointed out. Lastly, taking into account all pros and cons, we discuss the conditions and the intended aims of such collaboration